Pengaruh Label Halal dan Kemasan pada Produk Makanan Terhadap Minat Beli Konsumen - Yunia, Noorma; Budiman, Budiman; Albadiah, Ilmi; Soniah, Niah (STAI La Tansa Mashiro, 2025)
The background of this research highlights the importance of halal labels for Muslim consumers in Indonesia, who require guarantees of halal compliance for packaged food products. In Sindangsari Village, many residents have not yet paid attention to halal labels when purchasing products.This study aims to: 1. Determine the influence of the Halal label on food products towards consumer purchase intention in Sindangsari Village, Sajira District, Lebak, Banten, 2. Determine the influence of packaging on food products towards consumer purchase intention in Sindangsari Village, Sajira District, Lebak, Banten, and 3. Determine the influence of the Halal label and packaging on food products towards consumer purchase intention in Sindangsari Village, Sajira District, Lebak, Banten. The research method used is a correlational quantitative method. The population in this study consisted of 1,004 individuals aged 18-35 years from Sindangsari Village. The sampling technique used is nonprobability sampling with a purposive sampling category of 62 respondents. Data collection techniques include observation, literature review, questionnaires, and documentation. The data analysis techniques used are validity tests, reliability tests, normality tests, heteroscedasticity tests, multicollinearity tests, multiple linear regression analysis, determination coefficient tests, t-tests, and F tests, with the assistance of the Statistical Package for the Social Sciences (SPSS) software version 29. The results of the study show that: 1. The Halal label variable on food products partially has a positive and significant influence on consumer purchase intention in Sindangsari Village, Sajira District, Lebak, Banten, 2. The packaging variable on food products partially has a positive and significant influence on consumer purchase intention in Sindangsari Village, Sajira District, Lebak, Banten, 3. The Halal label and packaging variables on food products simultaneously have a positive and significant influence on consumer purchase intention in Sindangsari Village, Sajira District, Lebak, Banten. The contribution of the Halal label and packaging to consumer purchase intention is 31.00%, while the remaining percentage is influenced by other factors outside the research variables.